Learning Motivation as a Predictor of Mathematics Achievement: The Role of Visual, Auditory, Kinesthetic Learning Styles among Second Grade Angkasa Lanud Silas Papare Elementary School - Isnaini Nursafitri; Okky Rivwandha Imawan; Tri Suwarningsih (FKIP - Universitas Riau, 2026)
Mathematics learning in elementary schools is essential for developing students’ numeracy skills and foundational mathematical understanding. This study aimed to examine the effects of learning motivation and Visual–Auditory–Kinesthetic (VAK) learning styles on mathematics achievement among second-grade students at SD Angkasa Lanud Silas Papare. A quantitative ex post facto design with a correlational approach was employed. The participants consisted of 70 students selected through saturated sampling. Data on learning motivation and VAK learning styles were collected using validated and reliable questionnaires, while mathematics achievement data were obtained from test scores on addition and subtraction topics. Data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression. The results showed that learning motivation had a positive and significant effect on mathematics achievement (β = 1.328, p < .001), whereas visual, auditory, and kinesthetic learning styles did not have significant effects when analyzed simultaneously. The regression model explained 52.02% of the variance in mathematics achievement (R² = .5202). These findings indicate that learning motivation is a stronger predictor of mathematics achievement than VAK learning styles. Therefore, strengthening students’ motivation should be prioritized to improve mathematics learning outcomes in elementary schools.